Construction and Characterization of Conductometric Biosensor for Determination of the Diazinon Concentration - Prayoga, Indrajid; Mulyasuryani, Ani; Prasetyawan, Sasangka (Makara Journal of Science, 2014)
Excessive diazinon residue in vegetables can endanger human health. Therefore, a simple, fast, and accurate method is needed to detect residue. A conductometric biosensor is a good choice because it also offers high selectivity and sensitivity. The principle of detection of the conductometric biosensor is based on enzymatic hydrolysis of diazinon into O,O diethyl phosphorothiate,2-isopropyl-6-methylpyrimidin-4-ol, and H+ catalyzed by organophosphate hydrolase (OPH). The optimum amount of organophosphate hydrolase added to the screen-printed carbon electrode (SPCE) modified with BSA-glutaraldehyde is 118.5 µg, while the optimum pH is 8.5. This biosensor has a response time of 30 sec, a linear dynamic range of 0 to 1 ppm, sensitivity of 42.21 µS/ppm, and limit of detection of 0.19 ppm.